PENGARUH KETERAMPILAN GURU DALAM MENGELOLA KELAS TERHADAP HASIL BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Ginting, Rahmadani Fitri; Malinda, Dea Redha (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to analyze the factors influencing student learning outcomes in elementary schools, both partially and simultaneously. One of the factors suspected to have an impact is the teacher's skill in managing the classroom. This type of research is quantitative with an explanatory survey approach. The research population consists of 50 students, with the sample taken from all students in grades III and IV at SD Negeri 101829 Sei Glugur, Pancur Batu District. Data collection was carried out through questionnaires and documentation. The validity and reliability of the instruments were tested using factor analysis. Descriptive analysis results show that 92% of students fall into the good category for learning outcomes, while 85.05% of teachers' skills in classroom management also fall into the good category. The multiple regression analysis indicates a positive and significant effect of teachers' classroom management skills on student learning outcomes.